Effect of the temperature on the physical properties of the pure ionic liquid 1-ethyl-3-methylimidazolium methylsulfate and characterization of its binary mixtures with alcohols - Patricia F. Requejo (2014)
Experimental density, speed of sound, refractive index and viscosity data of the pure ionic liquid 1-ethyl3-methylimidazolium methylsulfate, [EMim][MSO4], were measured as a function of temperature from T = (293.15 to 343.15) K, every 5 K, and atmospheric pressure. Density, speed of sound and refractive index data were satisfactorily correlated with a linear equation, while viscosity data were fitted to the Vogel-Fulcher-Tamman (VFT) equation. Besides, from the experimental density values, the thermal expansion coefficient, alpha, was calculated. Furthermore, density and speed of sound for the binary systems of {methanol, or ethanol, or 1-propanol, or 2-propanol, or 1-butanol, or 1-pentanol + [EMim][MSO4]} were experimentally determined over the whole composition range, at T = (288.15, 298.15 and 308.15) K and p = 0.1 MPa. These properties were used to calculate the corresponding excess molar volumes and excess molar isentropic compressions, which were satisfactorily fitted to the Redlich-Kister equation. Finally, a comparison with available literature data was also carried out and the obtained results are discussed in terms of interactions and structure factors in these binary mixtures.